Perencanaan dan Pengadaan Obat di Puskesmas “X” Berdasarkan Permenkes Nomor 74 Tahun 2016 - Fathiyah Rahmah (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2018)
Imperfect and inaccurate drugs and medical consumables planning and procurement likely affect their sustainability in Public Health Center (Puskesmas). This paper aims to study the mechanism of drugs planning and procurement implemented by Puskesmas "X". This was a descriptive research using a qualitative approach and observational method. This study found there were two sources of drug financing and medical consumption in Puskesmas "X", using the Revenue and Expense Budgeting of the local administration and capitation funds from National Health Coverage program. Drugs planning was financed by the local government revenues and expenses budgeting scheme. Performed under the basis of annual drug usage report. The plannings were conducted at the end of the year to project next year drugs' consumption. Drugs procurement process was performed by preparing drugs consumption report and ordering sheet paper which then were submitted to drug logistics unit at Puskesmas "X". Afterward, the procurement process was performed by accessing e-catalog as the legal online system provided by the national government. This research concluded that the implementation of the planning and procurement of drugs in Puskesmas has fulfilled and followed Health Ministry Regulation Number 74 Year 2016.  Keywords : drugs planning, drugs procurement, regulationpublic health center